EFFECTIVENESS OF EXTRACT OF SOME MEDICINAL PLANTS AGAINST SOIL- BORNE FUSARIA CAUSING DISEASES ON LYCOPERSICON ESCULANTUM AND SOLANUM MELONGENA PLANTS - S.K. DWIVEDI; ENESPA (International Journal of Pharma and Bio Sciences, 2012)
The antifungal activity of extracts of Tinospora cordifolia (leaves), Moringa oleifera (bark) and Trachyspermum ammi (seeds) at three concentrations viz., 25, 50, 75% (v/v) were evaluated in vitro by poisoned food technique against Fusarium oxysporum f. sp. lycopersici and Fusarium solani causing wilt disease on tomato and brinjal plants. The antifungal activity was assessed in terms of percentage of inhibition of mycelial growth of the test fungi. All the plant extracts showed significant inhibition in the mycelial growth of the test pathogens. Among the extracts evaluated, M. oleifera against Fusarium oxysporum f. sp. lycopersici and T. cordifolia against Fusarium solani completely inhibited mycelial growth at 75% concentration followed by T. ammi seed extract.